Kolaborasi Pentahelix Dalam Pengembangan Desa Wisata Meat Kecamatan Tampahan Kabupaten Toba - Enjeli Mitami Batubara; Dewi Yanti; Muhammad Khadry (Universitas Negeri Medan, 2025)
This study analyzes the role and effectiveness of the Pentahelix collaboration (Government, Academics, Business, Community, and Media) in the development of Meat Tourism Village, located in Tampahan Subdistrict, Toba Regency. Meat Tourism Village holds great potential in natural tourism, cultural heritage, and local products, but the sustainability of its development heavily depends on the synergy among stakeholders. A qualitative research method using field interviews was employed to identify the internal and external participation of the Pentahelix actors. The results of the IFAS and EFAS analysis place Meat Tourism Village in Quadrant I of the SWOT matrix, indicating an aggressive position where strengths and opportunities significantly outweigh weaknesses and threats. The active participation of the tourism awareness group (Pokdarwis) and strong support from PT. INALUM are key strengths, while its inclusion in the Top 100 ADWI and central government support represent major opportunities. However, limited government budget and the threat of policy changes pose notable challenges. Therefore, the most appropriate development strategy is an aggressive strategy, which involves maximizing the full potential and collaboration of the Pentahelix stakeholders to promote comprehensive, sustainable, and community-based tourism village growth. Recommendations include establishing a regular Pentahelix coordination forum, improving the capacity of Pokdarwis and local communities through integrated training (hospitality, digital marketing, MSME management), and strengthening long-term collaboration with the education sector and businesses through MoUs and CSR programs. In addition, the Village Government and the Tourism Office should develop internal regulations and annual work plans that involve all Pentahelix elements as the foundation for the development of Meat Tourism Village. The implementation of this aggressive strategy will optimize the recognition from ADWI, the potential of MSMEs, and the trend of ecotourism to strengthen the position of Meat Tourism Village as a leading and sustainable tourist destination.